Delay in accessing definitive care for patients with microbial keratitis in Nepal - Hoffman, Jeremy J.; Yadav, Reena; Das Sanyam, Sandip; Chaudhary, Pankaj; Roshan, Abhishek; Singh, Sanjay K.; Mishra, Sailesh K.; Arunga, Simon; Hu, Victor H.; Macleod, David; Leck, Astrid; Burton, Matthew J. (Frontiers in Medicine, 2022)
Background The aim of this study was to describe the health-seeking journey for patients with microbial keratitis (MK) in Nepal and identify factors associated with delay. Methods Prospective cohort study where MK patients attending a large, tertiary-referral eye hospital in south-eastern Nepal between June 2019 and November 2020 were recruited. We collected demographic details, clinical history, and examination findings. Care-seeking journey details were captured including places attended, number of journeys, time from symptom onset, and costs. We compared “direct” with “indirect” presenters, analyzing for predictors of delay. Results We enrolled 643 patients with MK. The majority (96%) self-referred. “Direct” attenders accounted for only 23.6% (152/643) of patients, the majority of “indirect” patients initially presented to a pharmacy (255/491). Over half (328/643) of all cases presented after at least 7 days. The total cost of care increased with increasing numbers of facilities visited (p < 0.001). Those living furthest away were least likely to present directly (p < 0.001). Factors independently associated with delayed presentation included distance >50 km from the eye hospital [aOR 5.760 (95% CI 1.829–18.14, p = 0.003)], previous antifungal use [aOR 4.706 (95% CI 3.139–5.360)], and two or more previous journeys [aOR 1.442 (95% CI 1.111–3.255)]. Conclusions Most patients visited at least one facility prior to our institution, with time to presentation and costs increasing with the number of prior journeys. Distance to the eye hospital is a significant barrier to prompt, direct presentation. Based on these findings, improving access to eye care services, strengthening referral networks and encouraging early appropriate treatment are recommended to reduce delay, ultimately improving clinical outcomes.